2010
DOI: 10.3354/meps08777
|View full text |Cite
|
Sign up to set email alerts
|

Preferential feeding by the crab Necora puber on differing sizes of the intertidal limpet Patella vulgata

Abstract: The crab Necora puber L. is a common predator of limpets, the major grazer on rocky shores in Northern Europe. Information on interactions between crabs and their limpet prey is limited, extending mainly to limpet defensive and predator offensive tactics, while the importance of prey size on the outcome of such interactions remains largely unknown. Here, a laboratory approach was used to test for preference in feeding habits. Predation by N. puber with cheliped height 3 to 27 mm (carapace width [CW]: 16 to 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Most of the suspension feeders are sessile, and many of the grazers and predators are reasonably slow-moving and sedentary enabling removal and exclusion experiments. Work over the last 20 years, however, has emphasized the importance of mobile predators such as foraging by crabs (Silva et al, 2008(Silva et al, , 2010(Silva et al, , 2014Christofoletti et al, 2011) and fish (Taylor & Schiel, 2010) when the tide is in, and birds when the tide is out (Hockey & Underhill, 1984;Coleman et al, 1999;Coleman & Hockey, 2008) or by diving (e.g. eider ducks, Hamilton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the suspension feeders are sessile, and many of the grazers and predators are reasonably slow-moving and sedentary enabling removal and exclusion experiments. Work over the last 20 years, however, has emphasized the importance of mobile predators such as foraging by crabs (Silva et al, 2008(Silva et al, , 2010(Silva et al, , 2014Christofoletti et al, 2011) and fish (Taylor & Schiel, 2010) when the tide is in, and birds when the tide is out (Hockey & Underhill, 1984;Coleman et al, 1999;Coleman & Hockey, 2008) or by diving (e.g. eider ducks, Hamilton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of any predators was also recorded during these visual observations. Previous observations showed that the main tide-in predators were the crabs Necora puber (Linnaeus, 1767), Carcinus maenas (Linnaeus, 1758) and Cancer pagurus (Linnaeus, 1758) (Thompson et al ., 2000; confirmed by more recent work by Silva et al ., 2008, 2010 a , 2010 b ). Predation by floating gulls on emersed limpets at the waterline occurred very occasionally (RCT personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…It is a protandrous hermaphrodite, becoming sexually mature around 9 months transitioning from male to female at around 2-3 years (Orton et al 1956;LeQuesne and Hawkins, 2006). P. vulgata is preyed upon by a range of predators including crabs, fish (Silva et al 2004(Silva et al , 2008(Silva et al , 2010 and birds, including oystercatchers, Haematopus ostralegus del Hoyo and Collar, 2014 (Feare, 1971;Coleman et al 1999Coleman et al , 2004. Although juveniles are known to recruit into rock pools (Bowman and Lewis, 1977), as adults they are typically more abundant on emergent rock (i.e.…”
Section: Introductionmentioning
confidence: 99%